Parametric modelling of a wire electrical discharge machining process using path analysis approach. (2nd November 2022) - Sarker, Baneswar; Chakraborty, Shankar
ABSTRACT: This paper studies the application of a path analysis approach to model a wire electrical discharge machining (WEDM) process for investigating the relationships between its different process parameters and responses. It also estimates the contributive importance of the considered WEDM process parameters on each of the responses and identifies those parameters having the maximal influence on the responses. Four WEDM process parameters, i.e. pulse-on time, pulse-off time, spark gap voltage and wire feed are considered here as the independent variables, while three responses, i.e. cutting speed, gap current and surface roughness are treated as the dependent variables. This paper also proposes a new approach for modelling of the WEDM process, where one of the responses (gap current) is postulated to have an influence on the other two responses. Four different path analysis-based models are constructed with different sets of hypothesized relations. Based on the path analysis results, pulse-off time is identified as the most influential parameter for cutting speed, while pulse-on time is the most important parameter for both gap current and surface roughness. The calculated goodness-of-fit indices indicate the fitness with experimental data for all the four developed models while comparing their relative performance.